Acute right heart failure after hemorrhagic shock and trauma pneumonectomy—a management approach: A blinded randomized controlled animal trial using inhaled nitric oxide. Issue 2 (February 2017) - Lubitz, Andrea L.; Sjoholm, Lars O.; Goldberg, Amy; Pathak, Abhijit; Santora, Thomas; Sharp, Thomas E.; Wallner, Markus; Berretta, Remus M.; Poole, Lauren A.; Wu, Jichuan; Wolfson, Marla R.
Abstract : BACKGROUND: Hemorrhagic shock and pneumonectomy causes an acute increase in pulmonary vascular resistance (PVR). The increase in PVR and right ventricular (RV) afterload leads to acute RV failure, thus reducing left ventricular (LV) preload and output. Inhaled nitric oxide (iNO) lowers PVR by relaxing pulmonary arterial smooth muscle without remarkable systemic vascular effects. We hypothesized that with hemorrhagic shock and pneumonectomy, iNO can be used to decrease PVR and mitigate right heart failure. METHODS: A hemorrhagic shock and pneumonectomy model was developed using sheep. Sheep received lung protective ventilatory support and were instrumented to serially obtain measurements of hemodynamics, gas exchange, and blood chemistry. Heart function was assessed with echocardiography. After randomization to study gas of iNO 20 ppm (n = 9) or nitrogen as placebo (n = 9), baseline measurements were obtained. Hemorrhagic shock was initiated by exsanguination to a target of 50% of the baseline mean arterial pressure. The resuscitation phase was initiated, consisting of simultaneous left pulmonary hilum ligation, via median sternotomy, infusion of autologous blood and initiation of study gas. Animals were monitored for 4 hours. RESULTS: All animals had an initial increase in PVR. PVR remained elevated with placebo; with iNO, PVR decreased to baseline. Echo showed improved RV function in the iNO group while it remained impaired in the placebo group. After an initial increase in shunt and lactate and decrease in SvO2, all returned toward baseline in the iNO group but remained abnormal in the placebo group. CONCLUSION: These data indicate that by decreasing PVR, iNO decreased RV afterload, preserved RV and LV function, and tissue oxygenation in this hemorrhagic shock and pneumonectomy model. This suggests that iNO may be a useful clinical adjunct to mitigate right heart failure and improve survival when trauma pneumonectomy is required.